ORGANIZATIONAL ECONOMIC MECHANICS OF ACTIVITIES IN THE DIGITAL ECONOMY IN SAMARKAND CITY TRADE ENTERPRISES (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The active transition to the digital economy in Uzbekistan will be one of our top priorities for the next 5 years." Taking the definition of digital economy as "the activity of digital economy in the creation, distribution and use of digital technologies and related products and services, and the electronic generation, collection, storage, processing, transmission and presentation of information in digital technology", in the process of generalization in it, information about the processes of activity in the enterprise is digitized or brought into